2013
DOI: 10.1159/000356413
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Intravitreal Implant for Treatment of Patients with Persistent Diabetic Macular Edema

Abstract: Purpose: To report the 6-month anatomical and best-corrected visual acuity (BCVA) response after primary intravitreal dexamethasone implantation (Ozurdex®) in patients with refractory diabetic macular edema (DME). Methods: Retrospective review of the medical records of 58 patients with decreased visual acuity, due to refractory DME, who underwent a single injection of Ozurdex between November 2010 and January 2012, at the Instituto de Microcirurgia Ocular, Barcelona, Spain. Results: At baseline, the mean fovea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 23 publications
6
56
2
1
Order By: Relevance
“…These are mostly retrospective case series or prospective cohort studies, most of which demonstrated both anatomical and visual improvement at the end of follow-up [69][70][71][72][73][74][75][76][77]. The only randomised controlled trial assessing dexamethasone for anti-VEGF-resistant DMO found an anatomical benefit in combination with bevacizumab, but demonstrated no change in BCVA at 12 months [73].…”
Section: Anti-inflammatory Therapymentioning
confidence: 99%
“…These are mostly retrospective case series or prospective cohort studies, most of which demonstrated both anatomical and visual improvement at the end of follow-up [69][70][71][72][73][74][75][76][77]. The only randomised controlled trial assessing dexamethasone for anti-VEGF-resistant DMO found an anatomical benefit in combination with bevacizumab, but demonstrated no change in BCVA at 12 months [73].…”
Section: Anti-inflammatory Therapymentioning
confidence: 99%
“…The following studies by Bonnin et al, 48 Dutra Medeiros et al, 49 Bansal et al 50 and Totan et al 51 are summarised in Table 2. They are all similar studies with relatively short (4-6 month) follow-up.…”
Section: Review Diabetic Macular Oedemamentioning
confidence: 99%
“…51 The patient cohort in this study had not responded to previous anti-VEGF therapy and treatment may have been wearing off towards the end of the 6 months. The studies by Dutra Medeiros et al 49 and Bansal et al 50 specifically recruited patients with refractory/chronic DMO with encouraging results. With regards to adverse events, as might be expected IOP rises were observed, the majority of which were controlled with topical therapy or conservative management.…”
Section: Review Diabetic Macular Oedemamentioning
confidence: 99%
“…[80][81][82][83][84][85] In the first study, Zucchiatti et al 80 showed that a single intravitreal injection of Ozurdex produced improvement in BCVA and FT in eyes with persistent DMO. Such improvement was evident from the third day to the first month after injection, peaked at the third month and was no more significant 6 months after the injection.…”
Section: Interventional Case Series Studiesmentioning
confidence: 99%